2021
DOI: 10.1002/art.41732
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the DETECT Algorithm for Pulmonary Hypertension Screening in a Systemic Sclerosis Cohort

Abstract: Objective Pulmonary arterial hypertension (PAH) is one of the leading causes of mortality in systemic sclerosis (SSc). This study was undertaken to assess predictive accuracies of the DETECT algorithm and the 2015 European Society of Cardiology/European Respiratory Society (ESC/ERS) guidelines in SSc patients who underwent right‐sided heart catheterization (RHC) for pulmonary hypertension (PH) evaluation. Methods Patients with SSc who had diagnostic RHC, had no PH or had PAH, and had available data on variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…Our study confirms the high sensitivity of the DETECT algorithm, as already reported in previous studies [25][26][27][28]. There did not seem to be any PAH that went undiagnosed by DETECT in our work.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirms the high sensitivity of the DETECT algorithm, as already reported in previous studies [25][26][27][28]. There did not seem to be any PAH that went undiagnosed by DETECT in our work.…”
Section: Discussionsupporting
confidence: 92%
“…This new definition now includes PVR ≥ 3 WU as a diagnostic condition, whereas it had been unnecessary in the previous PAH definition. Using the updated PAH definition, Young et al [27] recently confirmed a sensitivity of 1 for the DETECT algorithm and of 0.8 for the ESC/ERS 2015 guidelines, even for patients with DLCO > 60% predicted. However, the reported specificity of DETECT decreased from 0.33 to 0.29 because of the application of the 2018 PAH definition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other causes of progressive symptoms such as pulmonary | 17 vascular disease or cardiac involvement should also be considered due to the multifactorial nature of SSc-associated manifestations. In SSc patients without ILD or with stable or controlled ILD after the first 3-5 years, annual PFTs are useful to monitor for both the onset and progression of SSc-ILD and to screen for SScassociated pulmonary arterial hypertension (PAH) (7,59).…”
Section: Definitions Risk Factors For and Monitoring Of The Progression Of Ssc-ildmentioning
confidence: 99%
“…After this period of close monitoring, all patients should undergo annual PFT, as late progression may occur despite long-term stabilization. Screening for other visceral manifestations, especially PAH, should also be continued according to published screening algorithms (59).…”
Section: A Proposed Strategy For the Management Of Ssc-ildmentioning
confidence: 99%